Pelaksanaan Administrasi Surat Menyurat dan Kearsipan Untuk Menunjang Akuntabilitas di Madrasah Tsanawiyah PAB 1 Sampali - Darmansah, Tengku; Affandi, Rizky Hasan; Tania, Fara Nabila; Bidawi, Hilwa Faza Nabila; Ayumi, Malika (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze and evaluate the implementation of correspondence and archiving administration at the MTS PAB 1 Sampali Organization. Correspondence administration and archives are crucial elements in the operations of educational organizations, ensuring smooth internal and external communications as well as systematic and secure document maintenance. The research methodology used is descriptive qualitative with data collection through observation, interviews and documentation. The results of the research show that the implementation of correspondence and archives administration at MTS PAB 1 Sampali has gone well even though there are several obstacles such as limited trained human resources and lack of use of information technology. Implementation of strict standard operational procedures and regular training for administrative staff is recommended to increase efficiency and effectiveness in managing correspondence and archives. Thus, it is hoped that this administrative optimization can support the achievement of educational and operational goals at MTS PAB 1 Sampali.